Metabolism of the lipophilic phycotoxin 13-Desmethylspirolide C using human and rat in vitro liver models. (1st June 2019) - Alarcan, Jimmy; Dubreil, Estelle; Huguet, Antoine; Aráoz, Romulo; Brée, Françoise; Bouaita, Belkacem; Hurtaud-Pessel, Dominique; Braeuning, Albert; Hessel-Pras, Stefanie; Lampen, Alfonso; Le Hégarat, Ludovic; Fessard, Valérie
Abstract: 13-Desmethylspirolide C (13-SPX-C) is a phycotoxin produced by dinoflagellates which can accumulate in shellfish. 13-SPX-C induces neurotoxic effects in rodents through blockade of nicotinic acetylcholine receptors. As no human intoxication has been to date attributed to the consumption of 13-SPX-C-contaminated seafood, this toxin is not regulated according to the Codex Alimentarius. Nevertheless, shellfish consumers can be exposed to 13-SPX-C via shellfish consumption. In order to follow the fate of the toxin after ingestion and to verify whether metabolic detoxification could explain the lack of human intoxications, we assessed the metabolism of 13-SPX-C using several in vitro liver systems. First, both phase I and II reactions occurring with rat and human liver S9 fractions were screened. Our results indicated that 13-SPX-C was almost completely metabolized with both rat and human liver S9. Using a receptor binding assay towards nicotinic acetylcholine receptors we demonstrated that the resulting metabolites showed less affinity towards nicotinic acetylcholine receptors than 13-SPX-C. Finally, we showed that 13-SPX-C induced a pronounced increase of gene expression of the drug-metabolizing enzyme cytochrome P450 (CYP) CYP1A2. The role of this CYP in 13-SPX-C metabolism was clarified using an innovative in vitro tool, CYP1A2-Silensomes™. In summary, this study highlights that liver first-pass metabolism can contribute to the detoxification of 13-SPX-C.